RECURRENT APHTHOUS STOMATITIS ASSOCIATED WITH PSYCHOLOGICAL FACTORS: A CASE REPORT - Afrizal Maulana; Nur Ariska Nugrahani (Journal of Health and Dental Sciences, 2026)
Recurrent aphthous stomatitis (RAS) is a common oral mucosal disorder characterized by recurrent painful ulcerations that may interfere with mastication, speech, and overall quality of life. The etiology remains unclear and is believed to be multifactorial, involving genetic predisposition, immune dysregulation, nutritional factors, microbiological influences, and psychological stress. This case report describes a female patient presenting with recurrent painful oral ulcers persisting for approximately one week, localized on the left buccal mucosa and right gingiva. The patient reported episodic gastroesophageal reflux, irregular sleep patterns, and high stress levels related to occupational demands, along with a history of childhood trauma. Clinical examination revealed well-defined ulcers with erythematous margins and yellowish bases, measuring approximately 5–7 mm in diameter. Hematological analysis was within normal limits, excluding systemic or hematologic disorders. A clinical diagnosis of recurrent aphthous stomatitis was established based on recurrence pattern, lesion characteristics, and absence of systemic involvement. Management included topical triamcinolone acetonide 0.1%, systemic methylprednisolone, and behavioral counseling focusing on oral hygiene, nutrition, and stress regulation. After one week of treatment, clinical improvement was observed, with complete ulcer resolution and minimal residual erythema. This case highlights the potential contribution of psychological stress and unresolved emotional trauma as aggravating factors in RAS and emphasizes the importance of a multidisciplinary approach, including pharmacological intervention, lifestyle modification, and psychological support in managing recurrent oral ulcers. DOI : 10.54052/jhds.v6n1.p1-10